Predicting BMX performance with laboratory measurements in elite riders - Moya-Ramón, M.; Haakonssen, E.; Peña-González, I.; Mateo-March, M.; Javaloyes, A. (Journal of Sports Sciences, 2022)
In Bicycle Motocross (BMX) performance is determined by the riders` sprint ability and power output. Therefore, descriptive and predictive performance assessments through laboratory and field tests are of interest. Twelve members of the Spanish BMX National Team performed 4 laboratory tests, including 1RM in squat, a Wingate test, a 5x6-s repeated sprint test (RST) and a force-velocity profile test. These tests were compared with the riders` field performance using the best lap of a simulated BMX competition consisting of 6 all-out laps on a standard BMX track. Pearson`s correlation and linear regression analysis showed a significant association (p < 0.05) between the riders` field performance and the 1RM (r = 0.84; R2 = 0.65), the peak power output in the RST (r = 0.87; R2 = 0.78) and the peak power, the mean power and the lactate production in the Wingate test (r = 0.68-0.77; R2 = 0.14-0.65), as well as maximal power from the force-velocity profile (r = 0.71; R2 = 0.53). The laboratory tests included in this study can show information about BMX riders` performance, with the highest values for the peak power obtained in the repeated sprint test (78% of the variance in common).